Between Tradition and Communication: Realigning Indonesian Maritime English Education with ELF Principles - Dolli Rotua Sinaga; Purnama N.F. Lumban Batu (Meteor STIP Marunda, 2024)
Maritime English (ME) is fundamental to ensuring safety in maritime operations and is recognized by the International Maritime Organization (IMO) as the official language at sea, serving as a lingua franca (ELF). To standardize ME instruction, the IMO has developed Model Course 3.17, advocating for an English for Specific Purposes (ESP) teaching approach. This study examines Indonesian maritime teachers' perceptions of ME and their integration of ELF and ESP principles into their teaching practices. Utilizing an online questionnaire with both closed and open-ended questions, the research uncovers a preference among teachers for adhering to native-speaker norms, despite a theoretical acknowledgment of the advantages of ELF. The findings highlight a discrepancy between the recognized needs of English as a Foreign Language (EFL) learners—who predominantly use English to communicate with other non-native speakers—and current teaching practices. This study calls for an alignment of ME instruction with the linguistic realities faced by mariners, advocating for the inclusion of ELF in pedagogical strategies to better prepare seafarers for global communication challenges.